Computational Exploration of Mechanistic Avenues in Metal‐Free CO2 Reduction to CO by Disilyne Bisphosphine Adduct and Phosphonium Silaylide. Issue 21 (22nd September 2021) - Dutta, Sayan; Singh, Kalyan; Koley, Debasis
Abstract: Recent years have seen a growing interest in metal‐free CO2 activation by silylenes, silylones, and silanones. However, compared to mononuclear silicon species, CO2 reduction mediated by dinuclear silicon compounds, especially disilynes, has been less explored. We have carried out extensive computational investigations to explore the mechanistic avenues in CO2 reduction to CO by donor‐stabilized disilyne bisphosphine adduct (R1 M ) and phosphonium silaylide (R2 ) using density functional theory calculations. Theoretical calculations suggest that R1 M exhibits donor‐stabilized bis(silylene) bonding features with unusual Si−Si multiple bonding. Various modes of CO2 coordination to R1 M have been investigated and the coordination of CO2 by the carbon center to R1 M is found to be kinetically more facile than that by oxygen involving only one or both the silicon centers. Both the theoretically predicted reaction mechanisms of R1 M and R2 ‐mediated CO2 reduction reveal the crucial role of silicon‐centered lone pairs in CO2 activations and generation of key intermediates possessing enormous strain in the Si−C−O ring, which plays the pivotal role in CO extrusion. Abstract : We have carried out extensive computational investigations to explore the mechanistic avenues in CO2 reduction to CO by donor‐stabilized disilyne bisphosphine adduct and phosphonium silaylide using density functional theory calculations. Both the theoretically predicted reaction mechanisms reveal the crucial role of silicon‐centered lone pairs in CO2 activations and generation of key intermediates possessing enormous strain in the Si−C−O ring, which plays the pivotal role in CO extrusion.